2016
DOI: 10.5702/massspectrometry.a0049
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Ribosomal Proteins of <i>Aspergillus fumigatus</i> for Use as Biomarkers in MALDI-TOF MS Identification

Abstract: We have previously proposed a rapid identi cation method for bacterial strains based on the pro les of their ribosomal subunit proteins (RSPs), observed using matrix-assisted laser desorption/ionization timeof-ight mass spectrometry (MALDI-TOF MS). is method can perform phylogenetic characterization based on the mass of housekeeping RSP biomarkers, ideally calculated from amino acid sequence information registered in public protein databases. With the aim of extending its eld of application to medical mycology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
13
0
2
Order By: Relevance
“…Functional annotation of the predicted genes was obtained from MycoCosm as described previously (5), which, in the case of the differentially expressed genes, was manually approved by examining the GO and KEGG terms and by blastp search. However, ribosomal subunits were named by homology with S. cerevisiae, as proposed by Nakamura et al (45).…”
Section: Methodsmentioning
confidence: 99%
“…Functional annotation of the predicted genes was obtained from MycoCosm as described previously (5), which, in the case of the differentially expressed genes, was manually approved by examining the GO and KEGG terms and by blastp search. However, ribosomal subunits were named by homology with S. cerevisiae, as proposed by Nakamura et al (45).…”
Section: Methodsmentioning
confidence: 99%
“…As the first step, we have investigated the actual state of information of RSPs of fungi registered in public protein databases through the characterization of ribosomal protein fractions extracted from genome-sequenced A. fumigatus strains as a model [ 28 ]. In our previous paper [ 28 ], we revealed that more than half of the amino acid sequences of RSPs registered in the public databases were incorrect, due chiefly to mis-annotation of exon/intron structures. We were able to successfully correct the sequence errors using a combination of in silico inspection by sequence homology analysis and MALDI–TOF MS measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Nakamura et al selected and verified 26 kinds of ribosomal subunit proteins (RSPs) whose molecular weights were under 16000 Da that could be used as biomarkers for A. fumigatus strains. 19 , 29 In conjunction with his study, we observed 20 kinds of RSPs that could be used as biomarkers when VITEK MS was used to identify our strains. Table 4 shows the RSP types selected in this study.…”
Section: Discussionmentioning
confidence: 53%